Electron spin resonance (ESR) spectroscopy of low-dimensional spin systems - Arango, Yulieth Cristina (Saechsische Landesbibliothek- Staats- und Universitaetsbibliothek Dresden, 2011)
The research in low-dimensional (low-D) quantum spin systems has become an arduous challenge for the condensed matter physics community during the last years. In systems with low dimensional magnetic interactions the exchange coupling is restricted to dimensions lower than the full three-D exhibited by the bulk real material. The remarkable interest in this field is fueled by a continuous stream of striking discoveries like superconductivity, quantum liquid and spin gap states, chiral phases, etc, derived from the strong effect of quantum fluctuations on the macroscopic properties of the system and the competition between electronic and magnetic degrees of freedom. The main goal of the current studies is to reach a broad understanding of the mechanisms that participate in the formation of those novel ground states as well as the characteristic dependence with respect to relevant physical parameters. In this thesis we present the results of an Electron Spin Resonance (ESR)-based study on different quasi-1D spin systems, exemplifying the realization of 1D-magnetic spin-chains typically containing transition metal oxides such as Cu2+ or V4+. The local sensitivity of the ESR technique has been considered useful in exploring magnetic excitation energies, dominant mechanisms of exchange interactions, spin fluctuations and the dimensionality of the electron spin system, among others. Aside from ESR other experimental results, e.g., magnetization and nuclear magnetic resonance besides some theoretical approaches were especially helpful in achieving a proper understanding and modeling of those low-D spin systems. This thesis is organized into two parts: The first three chapters are devoted to the basic knowledge of the subject. The first chapter is about magnetic exchange interactions between spin moments and the effect of the crystal field potential and the external magnetic field. The second chapter is a short introduction on exchange interactions in a 1D-spin chain, and the third chapter is devoted to ESR basics and the elucidation of dynamic magnetic properties from the absorption spectrum parameters. The second part deals with the experimental results. In the fourth chapter we start with the magnetization results from the zero-dimensional endohedral fullerene Dy3N@C80. This system is seemingly ESR “silent” at the frequency of X-band experiments. The fifth chapter shows an unexpected temperature dependence of the anisotropy in the homometallic ferrimagnet Na2Cu5Si4O14 containing alternating dimer-trimer units in the zig-zag Cu-O chains. In the sixth chapter different magnetic species in the layer structure of vanadium oxide nanotubes (VOx-NT) have been identified, confirming earlier magnetization measurements. Moreover the superparamagnetic-like nature of the Li-doped VOx-NT samples was found to justify its ferromagnetic character at particular Li concentration on the room temperature scale. In the seventh chapter the Li2ZrCuO4 system is presented as a unique model to study the influence of additional interactions on frustrated magnetism. The eighth chapter highlights the magnetic properties of the pyrocompound Cu2As2O7. The results suggest significant spin fluctuations below TN. The thesis closes with the summary and the list of references.